2012
DOI: 10.1111/j.2042-3306.2012.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an inertial sensor system of lameness quantification with subjective lameness evaluation

Abstract: The inertial sensor system was able to identify lameness at a lower level of sole pressure than the consensus of 3 equine veterinarians. The inertial sensor system may be an effective aid to lameness localisation in clinical cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
169
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(184 citation statements)
references
References 18 publications
(35 reference statements)
10
169
0
5
Order By: Relevance
“…Given the identical attachment method and the similar masses, effects are likely to be similar between the two IMUs. An IMU with comparable mass (less than 30g) shows good agreement with gold standard kinetic assessment and with subjective assessment (McCracken et al, 2012) indicating that clinically relevant signal components are maintained in the signal using this type of fixation.…”
Section: Sensor Fixationmentioning
confidence: 76%
“…Given the identical attachment method and the similar masses, effects are likely to be similar between the two IMUs. An IMU with comparable mass (less than 30g) shows good agreement with gold standard kinetic assessment and with subjective assessment (McCracken et al, 2012) indicating that clinically relevant signal components are maintained in the signal using this type of fixation.…”
Section: Sensor Fixationmentioning
confidence: 76%
“…Another possible reason could be that the ponies had unobservable mild lameness, such as a subclinical joint problem or chronic osteoarthritis, which results in an unequal swing range of the two limbs. McCracken et al [4] reported that objective lameness evaluation using an inertial sensor system would be able to detect lower levels of lameness compared to subjective lameness evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The inertial sensor technique has been in use for equine motion analysis, especially in the analysis of the trotting gait with the aims of improving sports performance and fine detection of lameness [4] as well as studying the differences in motion between types of horses [5] . Inertial sensor technology is highly sensitive and accurate with quantitative data, and is suitable for detection of even the slightest asymmetry in movement [6] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations